A comprehensive molecular phylogeny of tiger beetles (Coleoptera, Carabidae, Cicindelinae). (20th August 2018) - Gough, Harlan M.; Duran, Daniel P.; Kawahara, Akito Y.; Toussaint, Emmanuel F.A.
Abstract: Tiger beetles are a remarkable group that captivates amateur entomologists, taxonomists and evolutionary biologists alike. This diverse clade of beetles comprises about 2300 currently described species found across the globe. Despite the charisma and scientific interest of this lineage, remarkably few studies have examined its phylogenetic relationships with large taxon sampling. Prior phylogenetic studies have focused on relationships within cicindeline tribes or genera, and none of the studies have included sufficient taxon sampling to conclusively examine broad species patterns across the entire subfamily. Studies that have attempted to reconstruct higher‐level relationships of Cicindelinae have yielded conflicting results. Here, we present the first taxonomically comprehensive molecular phylogeny of Cicindelinae to date, with the goal of creating a framework for future studies focusing on this important insect lineage. We utilized all available published molecular data, generating a final concatenated dataset including 328 cicindeline species, with molecular data sampled from six protein‐coding gene fragments and three ribosomal gene fragments. Our maximum‐likelihood phylogenetic inferences recover Cicindelinae as sister to the wrinkled bark beetles of the subfamily Rhysodinae. This new phylogenetic hypothesis for Cicindelinae contradicts our current understanding of tiger beetle phylogenetic relationships, with several tribes, subtribes and genera being inferred as paraphyletic. Most notably, the tribe Manticorini is recovered nested within Platychilini including the genera Amblycheila Say, Omus Eschscholtz, Picnochile Motschulsky and Platychile Macleay. The tribe Megacephalini is recovered as paraphyletic due to the placement of the monophyletic subtribe Oxycheilina as sister to Cicindelini, whereas the monophyletic Megacephalina is inferred as sister to Oxycheilina, Cicindelini and Collyridini. The tribe Collyridini is paraphyletic with the subtribes Collyridina and Tricondylina in one clade, and Ctenostomina in a second one. The tribe Cicindelini is recovered as monophyletic although several genera are inferred as para‐ or polyphyletic. Our results provide a novel phylogenetic framework to revise the classification of tiger beetles and to encourage the generation of focused molecular datasets that will permit investigation of the evolutionary history of this lineage through space and time. Abstract : The first taxonomically comprehensive molecular phylogeny of Cicindelinae to date includes 328 taxa and nine gene fragments. Maximum‐likelihood phylogenetic inferences including or excluding ribosomal hypervariable regions recover Cicindelinae as sister to the wrinkled bark beetles (Rhysodinae). This new phylogenetic hypothesis for Cicindelinae contradicts our current understanding of tiger beetle phylogenetic relationships, with several tribes, subtribes and genera recovered as paraphyletic.